The first example of macrocyclic derivatives of cyclotetraphosphazene - Palabiyik, Duygu; Balci, Ceylan Mutlu; Besli, Serap (Taylor & Francis Ltd, 2021)
The alcoholysis reaction of octachlorocyclotetraphosphazene, N4P4Cl8 (1) with the disodium salt of tetraethyleneglycol gave the first macrocyclic cyclotetraphosphazene derivatives which are bis-ansa structures (2a and 2b). The isolated compound (2a) has been fully characterized by elemental analysis, MALDI-TOF mass spectrometry as well as H-1 and P-31 NMR spectroscopy. The molecular and crystal structure of 2a was determined by single crystal X-Ray diffraction. X-Ray crystallography confirms that the structure of 2a is the cis-bis-ansa isomer. This is the first example of a molecule of a tetrameric cyclophosphazene with a flexible macrocyclic organic substituent suitable for metal complexation.
Keywords: Cyclotetraphosphazene; diol; ansa; macrocyclic; crystal structure